Types of Code-Mixing in Indonesian Instagram Advertisements: A Linguistic Analysis Based on Muysken's Typology - Rayhan Hidayat; Cicilia Deandra Maya Putri (Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study investigates the types of code-mixing found in Indonesian Instagram advertisements based on Muysken's (2000) typology, which classifies code-mixing into three types: insertion, alternation, and congruent lexicalization. Ten Instagram advertisements from five different brands across various industries were selected as the data for this study. The advertisements were collected from five Indonesian brands active on Instagram between March and April 2026. The findings show that insertion is the most dominant type of code-mixing, appearing in nine out of ten advertisements, where English words and phrases are placed into Indonesian sentence structures. Alternation was found in only one advertisement, while congruent lexicalization was not found in any of the advertisements. These findings suggest that Indonesian advertisers predominantly use insertion as their preferred form of code-mixing, as English terms are widely recognized by target consumers and contribute to clearer and more effective communication in advertising.